Longitudinal impact of a pre‐populated default quantity on emergency department opioid prescriptions - Alexandra Carlson; Michael E. Nelson; Hina Patel (Journal of the American College of Emergency Physicians Open)
Abstract Objective Previously published studies indicate that a pre‐populated default quantity may decrease opioid amounts on discharge prescriptions from the emergency department (ED). However, the longitudinal effect of defaulted quantities has not been described in the literature. Methods A retrospective review of electronic health record data from visits to 4 hospital EDs in a community health system examined opioid prescription dispense quantities 3.5 years pre‐ and 6.5 years post‐implementation of a defaulted dispense quantity of seventeen. The primary purpose was to determine the percentage of ED discharge opioid prescriptions containing the prepopulated default dispense quantity after implementation. The longitudinal effect of a default quantity implementation on the average quantity prescribed (normalized per 1000 visits) was examined by comparing the pre‐implementation period (January 1, 2009–July 31, 2012) to the post‐implementation period (August 1, 2012–June 30, 2018). Results After implementation in 2012, the acceptance rate of the default dispense quantity increased each year, up to 48% in 2016 and maintained through 2018. A significant decrease in prescribed opioid quantities post‐default quantity implementation was sustained, with the average quantity prescribed from 2015–2018 maintained at 17 or lower. Conclusion A pre‐populated default quantity impacts discharge opioid prescribing as evidenced by a high sustained rate of prescriber utilization over years and reduction in the per prescription average pill quantity. The acceptance of a pre‐populated default quantity may allow for selection of even a lower quantity to influence prescribing patterns of opioid analgesics.